Impact factors and reference range upper limit of thyroid volume in children aged 8-10 years old in Huangpu District, Shanghai - Weihua CHEN; Chengdi SHAN; Lili SONG; Lifang MA; Yun CAO; Youshun QIAN; Aina HE; Jun XIAO (环境与职业医学)
BackgroundAs one of the key populations in the prevention and treatment of iodine deficiency disorders, it is important to continuously monitor the iodine nutritional level of school-age children. The current reference interval for thyroid volume in China is based on age only, without taking into account differences in individual developmental levels, and the distribution of thyroid volume may vary regionally due to economic, demographic, and environmental factors. The current reference cut-off points for thyroid volume proposed by the World Health Organization are not based on the Chinese population.ObjectiveTo understand the iodine nutritional status and distribution of thyroid volume (Tvol) among children aged 8-10 years in Huangpu District, Shanghai, China, to identify impact factors of Tvol, and to propose a reference range upper limit for local thyroid health surveillance, so as to provide a basis for goiter control and prevention.MethodsSix hundred children aged 8-10 years in Huangpu District were recruited in 2017, 2020, and 2023, and body height, weight, thyroid volume, urinary iodine, and iodine content of household edible salt were determined. A multilevel model was constructed using population density and area as regional variables, and age, body surface area (BSA), and body mass index (BMI) as potential impact factors for at the individual level, to assess their effects on thyroid volume. Quantile regression of thyroid volume was performed, and the 98th percentile (P98) of thyroid volume was predicted based on age and BSA.ResultsThe iodized salt coverage in the households of surveyed children in 2017, 2020, and 2023 was 72.0%, 57.0%, and 48.0%, respectively, and the iodized salt coverage decreased by year (χ2=24.31, P<0.001). The urinary iodine level of children in 2017 was higher than that in 2020 and 2023 (χ2=18.77, P<0.001). The Tvol medians of children in 2017, 2020, and 2023 were 2.29, 2.49, and 2.97 mL, respectively, and the Tvol increased by year (χ2=60.04, P<0.001). The proportion of goiter was higher in children in 2023 than in 2017 and 2020 (χ2=6.57, P<0.05). Sex differences were not statistically significant for urinary iodine levels, thyroid volume, and goiter. The median Tvol was 2.26, 2.58, and 2.76 mL in children of 8, 9, and 10 years old respectively, and the Tvol increased with age (χ2=49.02, P <0.001). Tvol was positively correlated with age, BSA, and BMI with correlation coefficients of 0.2846, 0.3723, and 0.2950, respectively. The final quantile regression model showed that the strongest effect of BSA was associated with the 98th percentile of Tvol. Multilevel models considering population density or area as regional variables failed to achieve convergence.ConclusionTo establish the upper limit of the reference interval for thyroid volume of healthy children in Huangpu District, the effects of age and BSA should be considered at the individual level, and the upper limit of the normal interval for goiter screening is suggested to be the 98th percentile value of BSA at the same age. In addition, the adaptability of population density and regional area as indicators of regional aggregation of thyroid volume distribution still needs to be further explored.